CHA2DS2-VASc-HSF score calculation and its comparison with the severity of coronary artery disease (CAD) in patients undergoing coronary angiography (Journal of Invasive and Clinical Cardiology, 2025)
Background: CHA2DS2-VASc score has been widely used in atrial fibrillation patients to predict the risk of thromboembolism. The new CHA2DS2-VASc-HSF score has additional risk factors of atherosclerosis and thus evaluates the risk of CAD and predict its severity. Our study aims to assess CHA2DS2-VASc-HSF score and compare it with the severity of CAD by Gensini score among Nepalsese population.Methods: This is a prospective, hospital based, cross-sectional observational study conducted in SGNHC and Bir Hospital, Kathmandu, Nepal. Our study included 100 patients who underwent coronary angiography for the diagnosis of CAD after meeting inclusion criteria from July 2023 to June 2024. CHA2DS2-VASc and CHA2DS2-VASc-HSF score were calculated in all patients and compared to vessel score and Gensini score.Results: Out of 100 patients, 55 patients were males and 45 patients were females. The most common risk factor was hypertension. Majority of patients having CHA2DS2-VASc score ³2 and CHA2DS2-VASc-HSF score ³2.5 had severe CAD (p-value